Die verborgene Schönheit der Natur: die Sicht des Physikers - Pirner, Hans J. (Heidelberger Jahrbücher online, 2019)
The article “The hidden beauty of nature” starts with a differentiation of beauty in art and science. The view of a physicist defines scientific aesthetics as a beautiful combination of intuition visualized in tables, graphs and pictures with simple explanations of the underlying laws of nature. Examples come from different subjects: Time, space, time-space and space-time, matter and forces. Physics makes time become visible by uniform oscillations. Decay curves of elements allow us to go back into the prehistory of the earth. Euclidean and curved spaces define our earth. Satellites built according to modern science present us with a magnificent picture of our earth from outside. Light propagating with finite speed confines the past and future of any event. The beautiful pattern of cosmic (microwave) radiation from space lets us go back to the big bang. Atomic structure shows up in macroscopic crystals, and modern tunnelling microscopes depict even single atoms, whereas the smaller elementary particles need modern detectors to map out their tracks and underlying symmetries.
Gesehen am 10.10.2019